Peran Orang Tua dalam Pendidikan Keterampilan Hidup (Life Skill) Anak Usia Dini - Aulia, Putri; Batubara, Hafifah; Sit, Masganti (Lembaga Yasin AlSys, 2025)
The role of parents is very important in life skills education for early childhood, because at this stage children are in a period of rapid development both cognitively, emotionally, socially and physically. Life skills education includes basic skills such as the ability to be independent, regulate emotions, communication, and the ability to face daily challenges which will help children to become strong and independent individuals. This research aims to examine the role of parents in guiding, providing examples, and creating an environment that supports the development of children's life skills. This research method uses a qualitative approach with interview techniques and observations of parents and young children. The research results show that parents' active involvement, both in providing stimulation, emotional support, and organizing daily routines, has a positive impact on children's life skills. Parents who understand the importance of life skills and are involved in their children's learning process are able to help their children develop independence and self-confidence from an early age.